Simulating anomalous dispersion in porous media using the unstructured lattice Boltzmann method - Misztal, Marek K.; Hernandez-Garcia, Anier; Matin, Rastin; Müter, Dirk; Jha, Diwaker; Sørensen, Henning O.; Mathiesen, Joachim (Frontiers in Physics, 2015)
Flow in porous media is a significant challenge to many computational fluid dynamics methods because of the complex boundaries separating pore fluid and host medium. However, the rapid development of the lattice Boltzmann methods and experimental imaging techniques now allow us to efficiently and robustly simulate flows in the pore space of porous rocks. Here we study the flow and dispersion in the pore space of limestone samples using the unstructured, characteristic based off-lattice Boltzmann method. We use the method to investigate the anomalous dispersion of particles in the pore space. We further show that the complex pore network limits the effectivity by which pollutants in the pore space can be removed by continuous flushing. In the smallest pores, diffusive transport dominates over advective transport and therefore cycles of flushing and no flushing, respectively, might be a more efficient strategy for pollutant removal.